A comparative analysis of microplastics in feces of terrestrial mammalian wildlife around Hong Kong - Mariella Siña; Alexander Kunz; Christelle Not; Sofia Ya-Hsuan Liou (Scientific Reports)
Abstract Plastic ingestion by terrestrial mammals, especially wildlife near urbanized areas, remains underexplored, with limited studies exploring species-specific differences. This study addresses these gaps by examining microplastics (MPs) in feces of five wild species from Hong Kong’s countryside: buffalo, cattle, wild boar, macaques, and porcupines. These species were selected for their high interaction with humans and consumption of anthropogenic food. Fecal samples were digested, visually inspected, and MPs characterized using spectroscopy. Microplastics were detected across all sites: macaques (0.2–6.9 MPs/gram dry weight [d.w.], 50–90% occurrence), boars (0.5–3.7 MPs/gram d.w., 60–100% occurrence), porcupines (2.1 MPs/gram d.w., 80% occurrence), buffalo (17.7 MPs/gram d.w., 100% occurrence), and cattle (4.1–65.5 MPs/gram d.w., 90–100% occurrence). Secondary microplastics, primarily polyethylene, polypropylene, and polyester (common in food packaging and textiles) were predominant. Feeding behaviour significantly influenced microplastic abundance. Non-selective grazers (buffalo and cattle) exhibited higher concentrations (median: 15.8 and 17.7 MPs/gram d.w., respectively) compared to selective feeders (macaques, porcupines, and boars; median: 1.8, 2.1, and 1.2 MPs/gram d.w.). Regarding MPs size, the larger mammals, cattle and buffalo, excreted significantly larger microplastics (522 and 391 µm) compared to macaques and porcupines (301 and 268 µm). We present the first evidence of plastic ingestion by common wildlife species from Hong Kong, emphasizing the vulnerability of animals to plastic pollution in peri-urban habitats. The findings underscore the need for research on the health impacts of plastic ingestion and the development of strategies to mitigate plastic pollution to natural ecosystems.